The pathos of freedom and the logos of rationality in Manuel González Prada - Godenzi Alegre, Jorge Luis (2018)
It seeks to determine the relationship between pathos and logos in Don Manuel González Prada. The pathos for freedom was the beginning of public behavior in Manuel González Prada and the logos of rationality were at his service. In his thought process is described constituent rational conjecture and the prediction, it is concluded that both concepts are clearly connected to his work despite his attempt to make freed on the strongest passion. Are the grounds of “discreet pleas rues of intelligence” and “Secret Adventures of order” said the bright Borges.